Pendampingan Pembelajaran Fiqih Melalui Model Problem Based Learning Untuk Meningkatkan Hasil Belajar Siswa MTs Nurul Yaqin Pengkol Tambakrejo Bojonegoro - Dhurotun Nasikah; Roma Aristiyanto; Salafudin Salafudin; Umi Mahmudah (IAINU Kebumen, 2023)
The activity of mentoring fiqh learning through the problem-based learning (PBL) model at MTs Nurul Yaqin Pengkol Tambakrejo Bojonegoro aims to enhance students' learning outcomes and the quality of religious education. The study involved 30 participants from the 8th grade at MTs Nurul Yaqin Pengkol for the academic year 2022/2023. The mentoring activity was conducted in three stages, namely planning, implementation, and monitoring. The results indicate that the mentoring activity proceeded smoothly and successfully, contributing positively to students' learning outcomes. Active student participation, deeper understanding of fiqh concepts, and enhanced critical and creative thinking skills were significant outcomes of the PBL model mentoring. Mentoring fiqh learning through the PBL model significantly contributed to students' learning outcomes at MTs Nurul Yaqin Pengkol Tambakrejo Bojonegoro. The PBL model proved effective in improving the quality of learning and addressing challenges in fiqh learning processes. The implications of this activity encompass improved learning quality, students' learning outcomes, as well as the development of critical and creative thinking skills. Additionally, the activity fostered increased interest and motivation for learning among students, providing a positive impact on religious education at the madrasah.